Ampiang Dadiah: Functional Packaging Design For Minangkabau Traditional Food - Afdhal, Vernanda Em; Affandi, Syawlani (Aliansi Desainer Produk Industri Indonesia (ADPII), 2024)
Dadih, or Dadiah in Minangkabau, is a traditional yogurt made from fermented buffalo milk. The fermentation process takes place in bamboo segments, which are sealed with banana leaves. Ampiang Dadiah is a combination of ampiang (flattened glutinous rice), gulo anau (palm sugar), and dadiah. This dish is a source of pride for the Minangkabau community, known for its many benefits and containing lactic acid bacteria that act as probiotics. However, traditional foods like this are often hard to find and not widely known. The preparation is inconvenient, and there is no packaging that combines dadiah, gulo anau, and ampiang. The presentation is also less attractive, preventing it from becoming a signature souvenir from West Sumatra. To address these issues, a packaging design for ampiang dadiah has been created that retains local wisdom while integrating modern packaging elements. This innovation includes new packaging for dadiah, which is traditionally wrapped in bamboo and sealed with banana leaves or plastic. The new design features attractive packaging with instant ampiang, making it easy to enjoy at any time. The design process followed the Design Thinking method, considering aspects such as empathize, define, ideate, prototype, and test. The new design makes the traditional ampiang dadiah easier to serve, combines it with gulo anau and ampiang in one package, and is presented attractively, informatively, and with higher market value. The result is a functional and modern packaging design that serves as an inspiration and an effort to elevate local products to become a hallmark of West Sumatra.